Numerical Calculation and Analysis of Cycloidal Gear Wear Amount of RV Reducer - Jianxin Su; Chen Li (Jixie chuandong)
Based on the Archard wear model and the Hertz contact theory， the meshing area of the cycloid gear profile is discretized，and a calculation model for the wear process of the cycloid gear is established. According to the calculation model， the relationship between the sliding coefficient，wear rate，the wear deep and the engagement angle at each meshing point are analyzed， and the curve fitting is carried out. The results show that the established numerical calculation method can realize the quantitative calculation of the wear amount of the tooth profile of the cycloid pinwheel under different repair methods，different repair amounts，and different working conditions.